INTERANNUAL VARIATION IN THE PHENOLOGICAL BEHAVIOR OF TWO NATIVE TREE SPECIES IN ALLUVIAL FOREST - Milani, Jaçanan Eloisa de Freitas; Roderjan, Carlos Vellozo; Kersten, Rodrigo de Andrade; Galvão, Franklin; Amano, Erika; Jantsch, Denize Beatriz (Floresta, 2022)
The vegetative (senescent leaf, mature leaf and budding) and reproductive (bud, anthesis, unripe fruit and ripe fruit) phenological behavior of Gymnanthes klotzschiana (Euphorbiaceae) and Blepharocalyx salicifolius (Myrtaceae) were evaluated for 5 years in a fragment of Alluvial Mixed Ombrophilous Forest in southern Brazil, by the intensity index, seeking to answer the following questions: (i) Do phenological events follow an annual pattern or is there variation over the period? (ii) Which meteorological variables, among temperatures (minimum, mean and maximum) and precipitation, influence the phenophases? Phenological data were correlated with precipitation and minimum, mean and maximum temperatures of the study period. Variations in the intensity of the phenophases were detected between the years analyzed. Correlations with temperatures were identified for some phenophases during the study period. The species showed similar phenological behavior in vegetative phenophases, but variations in the intensity of the phenophases were detected between the years analyzed, which may be responses to annual temperature and precipitation variations. With the obtained data of correlation between the phenophases and the meteorological variables, it was possible to conclude that different meteorological signals are felt by the plants to express their phenophases. It seems that there is a tendency for temperatures to be an important factor that regulates plant phenology, but that the monitoring period may also influence these factors